2021
DOI: 10.1021/acsenergylett.1c01214
|View full text |Cite
|
Sign up to set email alerts
|

Double-Site Substitution of Ce into (Ba, Sr)MnO3 Perovskites for Solar Thermochemical Hydrogen Production

Abstract: Solar thermochemical hydrogen production (STCH) is a renewable alternative to hydrogen production using fossil fuels. While serial bulk experimental methods can accurately measure STCH performance, screening chemically complex materials systems for new promising candidates is more challenging. Here we identify double-site Ce-substituted (Ba,Sr)­MnO3 oxide perovskites as promising STCH candidates using a combination of bulk synthesis and high-throughput thin-film experiments. The Ce substitution on the B-site i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This experimental workflow at NREL has been benchmarked against other laboratories. 14 , 15 Other publications demonstrate the range of materials chemistries (e.g., oxides, 16 nitrides, 17 chalcogenides, 18 Li-containing materials, 19 intermetallics) 20 and properties (e.g., optoelectronic, 21 electronic, 22 piezoelectric, 23 photoelectrochemical, 24 thermochemical) 25 to which these HTE methods have been applied.
Figure 2 Experimental and data workflows for high-throughput materials research The workflow starts with (A) experiment design, then material samples are (B) produced, (C) treated, (D) measured, and (E) stored in archives.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This experimental workflow at NREL has been benchmarked against other laboratories. 14 , 15 Other publications demonstrate the range of materials chemistries (e.g., oxides, 16 nitrides, 17 chalcogenides, 18 Li-containing materials, 19 intermetallics) 20 and properties (e.g., optoelectronic, 21 electronic, 22 piezoelectric, 23 photoelectrochemical, 24 thermochemical) 25 to which these HTE methods have been applied.
Figure 2 Experimental and data workflows for high-throughput materials research The workflow starts with (A) experiment design, then material samples are (B) produced, (C) treated, (D) measured, and (E) stored in archives.
…”
Section: Resultsmentioning
confidence: 99%
“…This experimental workflow at NREL has been benchmarked against other laboratories. 14,15 Other publications demonstrate the range of materials chemistries (e.g., oxides, 16 nitrides, 17 chalcogenides, 18 Li-containing materials, 19 intermetallics) 20 and properties (e.g., optoelectronic, 21 electronic, 22 piezoelectric, 23 photoelectrochemical, 24 thermochemical) 25 to which these HTE methods have been applied.…”
Section: Descriptormentioning
confidence: 99%
“…Doping scheme of perovskites is another research content, and a series of doped perovskites as redox materials have been reported. 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 Typical perovskites materials include lanthanum-manganite perovskites, lanthanum-cobalt perovskites, and yttrium-manganese perovskites. For lanthanum-manganite perovskites, the most studied is La 1− x Sr x MnO 3 .…”
Section: Solar-driven Thermochemical Conversionmentioning
confidence: 99%
“…Oxide materials with perovskite structure constitute a large and versatile class of compounds characterized by a general formula of ABO 3 , where numerous A and B metal elements can be accommodated . These materials exhibit a wide spectrum of electrical properties, from metallic or superconducting to semiconducting or insulating, thus rendering them subjects of extensive exploration across various applications. , Notably, perovskite compounds doped with acceptor ions have gained substantial attention due to their efficacy as solid electrolytes in proton-conducting solid oxide electrolysis cells (H-SOECs) and solid oxide fuel cells (SOFCs), solar thermochemical hydrogen production (STCH), and chemical sensors . These electrochemical applications are enabled by the facile transport of protons within the perovskite lattice, which is characterized by low activation barriers for high proton conductivity .…”
Section: Introductionmentioning
confidence: 99%